Effects of beam and magnetic field parameters on highly competing TE 01 and TE21 modes of vane loaded gyro-TWT - Singh G.; Kartikeyan M.V.; Sinha A.K.; Basu B.N. (My University, 2025)
In this paper, the dispersion relation for a vane-loaded cylindrical waveguide, considering the azimuthal harmonic effects arising from the azimuthal periodicity of the vanes, excited in transverse electric (TE) modes and the gain for a gyro-TWT have been presented. The effects of beam and magnetic field parameters on two highly competing modes have been studied.